THE ROLE OF MUSIC IN FOLK BALLAD PERFORMANCE - Eldorbek Erkin og’li Khamitov; Turdimuratova Mexribanu Janabaevna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract Music has been a fundamental aspect of folk ballads, shaping both their performance and their transmission as a form of oral tradition. This study examines the intricate relationship between music and storytelling, highlighting how musical components influence narrative structure, emotional resonance, and audience engagement. Using a combination of historical investigation, performance analysis, and literary study, the research explores the ways in which melody, rhythm, vocal techniques, and instrumental accompaniment contribute to the memorability, interpretive richness, and cultural significance of traditional ballads. The analysis demonstrates that music is not merely an ornamental addition but a core element of the ballad’s communicative power. Rhythmic patterns and metrical alignment interact with narrative pacing, while melodic motifs, harmonies, and recurring musical phrases underscore thematic content, emphasize dramatic tension, and amplify emotional impact. Repetition in both lyrics and melody serves a mnemonic purpose, aiding oral transmission and allowing these ballads to persist across generations. Instrumentation, ranging from simple string instruments to more elaborate ensembles, provides performers with expressive tools to convey mood, character, and subtle narrative nuances. In addition, this study considers the performative and social dimensions of ballad music, showing how it fosters audience participation, communal connection, and cultural identity. Through musical performance, listeners are engaged collectively, reinforcing shared memory, moral values, and community cohesion. In historical contexts with limited literacy, music ensured accessibility and maintained the relevance of ballads as tools for storytelling, education, and social integration. In conclusion, music is inseparable from the function and impact of folk ballads, providing structure, enhancing emotional expression, and sustaining cultural heritage. By analyzing the role of music in performance, this research illustrates how melody, rhythm, and instrumentation work in tandem with narrative, enriching the interpretive experience and ensuring the enduring significance of ballads within the oral tradition.